The Proceedings of the Third International Conference on Communications, Signal Processing, and Systems - Mu, Jiasong; Liang, Qilian; Wang, Wei; Zhang, Baoju; Pi, Yiming (Lecture Notes in Electrical Engineering,, 2015)
The Proceedings of The Third International Conference on Communications, Signal Processing, and Systems provides the state-of-art developments of communications, signal processing, and systems. This book is a collection of contributions from the conference and covers such topics as wireless communications, networks, systems, and signal processing for communications. The conference was held July 2014 in Hohhot, Inner Mongolia, China.